2002
DOI: 10.1042/ba20020001
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and cloning of a chitinase from Bacillus sp. NCTU2

Abstract: A chitin-degrading Bacillus strain, designated as NCTU2, was screened from soil and identified. An extracellular chitinase was purified to >90% homogeneity from the culture filtrate. The purification involved hydrophobic-interaction and gel-filtration chromatographic separations with a yield of 58%. The purified enzyme (ChiNCTU2) is a monomeric protein with an estimated molecular mass of 36.5 kDa and a pI of 6.3. It is thermally stable at 60 degrees C and pH 6-8 for more than 3 h. The optimal activity is in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(81 citation statements)
references
References 0 publications
2
76
0
3
Order By: Relevance
“…Only few reports have shown that bacterial chitinases is stable at broad range of pH. The molecular basis for retaining of activity and stability at high pH of the enzyme remains to be elucidated [6][7][8][9]. The optimum temperature for the enzyme activity was found to be 55°C at pH 6.0 (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Only few reports have shown that bacterial chitinases is stable at broad range of pH. The molecular basis for retaining of activity and stability at high pH of the enzyme remains to be elucidated [6][7][8][9]. The optimum temperature for the enzyme activity was found to be 55°C at pH 6.0 (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…is regarded as a group of bacteria particularly efficient in the breaking down of chitin [5]. However, only a few thermostable chitinolytic enzymes from bacteria have been reported [6][7][8][9]. Previously, thermostable chitinases have been isolated from Bacillus licheniformis MB-2 [8] and Streptomyces thermoviolaceus OPC-520 [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial species such as Bacillus , Pseudomonas , Serratia and Arthrobacter have been proved in controlling the fungal diseases (Joseph et al 2007) Earlier reports showed that microorganisms capable of lysing chitin, which is a major constituent of the fungal cell wall, play an important role in biological control of fungal pathogens (Yu et al 2002; Zhang and Fernando 2004; Abdullah et al 2008). Fungi such as Trichoderma and bacteria such as Bacillus , Serratia and Alteromonas were reported to have chitinolytic activity (Mabuchi et al 2000; Someya et al 2001; Wen et al 2002; Huang et al 2005; Viterbo et al 2001). Non-pathogenic soil Bacillus species offer several advantages over other organisms as they form endospores and hence can tolerate extreme pH, temperature and osmotic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…And, plants produce chitinase enzyme to defend themselves against fungal pathogens [9]. The baculoviruses used in biological control of insect pests produce chitinase for pathogenicity [10]. Chitooligosaccharides are produced via chitinase enzyme.…”
Section: Introductionmentioning
confidence: 99%